“Unpaid work”: on the pitfalls of metaphorical redescription: comment on Jason W. Moore's Capitalism in the Web of Life (Verso 2015) - Schlaudt, Oliver (Zeitschrift für kritische Sozialtheorie und Philosophie, 2017)
I am commenting on Moore's book from the perspective of philosophy of science, i. e. I concentrate on his conceptual framework and its formal features. There are two such features which will immediately attract the attention of any philosopher: first, the use of quotation marks, which I take to indicate that the author does not really wish (or dare, perhaps) to say what he actually says and, second, claims of necessity or counterfactual conditionals, which demand especially robust argumentation. These two features are directly related to each other: (1) Moore places the category of unpaid work, at least occasionally, in quotation marks; this concept is fundamental to his approach and he uses it in a much broader sense than is commonly done; and (2) he claims that capitalism depends necessarily on inputs of unpaid work. In my comment, I will discuss a number of conceptual problems linked to Moore's extension of the notion of unpaid work and will analyze the extent to which these problems affect his claim that capitalism is necessarily dependent on unpaid work
Gesehen am 21.10.2020
Keywords: Rezension